THE USE OF ANIMATED MEDIA ON SHOOTING LEARNING OUTCOMES IN BASKETBALL GAMES IN CHILDREN AGED 10-11 YEARS - Yopi Meirijal; Sumbara Hambali; Sony Hasmarita; Yovhandra Ockta (Program Studi PGSD Universitas Flores, 2025)
This study investigates the effectiveness of animated media in improving basketball shooting performance among children aged 10–11 years through an experimental method, revealing that animation-based instruction significantly enhances training outcomes compared to conventional methods. The research was conducted at Cimahi Mandiri 2 Elementary School with a total of 40 students participating in extracurricular basketball activities. Using a total sampling technique, participants were randomly divided into two equal groups: one received animated media during training, and the other followed traditional instruction without animation. A basketball shooting test was used to assess performance improvements. The results demonstrated that the group exposed to animated media showed a significant increase in shooting performance (t=23.59>t-table=2.262), while the non-animation group also improved but to a lesser extent (t=12.68>t-table=2.262). Furthermore, a comparative test between the two groups yielded a significant difference (t=25.98>t-table=2.101), indicating a stronger impact of animated media. In conclusion, animated media significantly improves basketball shooting skills in children, and the results and conclusions are consistent with the study’s objectives.